Needle grass-like cobalt hydrogen phosphate on Ni foam as an effective and stable electrocatalyst for the oxygen evolution reaction. Issue 65 (29th July 2019) - Sun, Zemin; Yuan, Mengwei; Lin, Liu; Yang, Han; Li, Huifeng; Sun, Genban; Yang, Xiaojing; Ma, Shulan
Abstract : Novel three dimensional needle grass-like CoHPO4 ·H2 O on Ni foam has been prepared as an effective and robust OER electrocatalyst. Abstract : Exploring efficient non-precious metal electrocatalysts for the oxygen evolution reaction (OER) is a challenging task in sustainable energy systems. Herein, facile and novel three dimensional (3D) needle grass-like CoHPO4 ·H2 O on Ni foam (CoHPO/NF) has been prepared as an effective and robust OER electrocatalyst for the first time. The unique 3D topological structure of CoHPO exposes more electrocatalytic active sites and facilitates mass transport. The coordinated HPO4 2− anions work as OH − traps to synergistically enhance the process of the OER. Because of these advantages, it exhibits an extraordinary OER performance with a low overpotential of only 350 mV at 50 mA cm −2 . Notably, it also exhibits excellent long-term stability. According to the theoretical calculations, the electron structure of the Co was significantly influenced by the coupled HPO4 2− species, which leads to superior activity for the OER. All the findings imply that CoHPO/NF is a promising material to substitute for noble metals in overall water splitting.